Yield strength and misfit volumes of NiCoCr and implications for short-range-order - Binglun Yin (Nature Portfolio, 2020)
Chemical short-range order (SRO) NiCoCr has been proposed to account for its positive stacking fault energy and good mechanical properties. Here, a combination of theory and experiment shows that SRO is of negligible importance in NiCoCr processed by standard methods.